The importance of talent management: a study of Chinese organisations - Liu, Yi; Pearson, Cecil (Emerald Group Publishing Limited, 2014)
Purpose – This paper aims to investigate the importance of talent management (TM) as a fundamental component of management philosophy and practice to auger contemporary competitiveness in Chinese organisations, which have forged transformational synergies with traditional forms of political intervention and capital investment. Design/methodology/approach – A pluralist design was used, in which the quantitative and qualitative assessment was adopted with Chinese decision-making executives of corporations operating in the global arena. By using managerial responses, this paper offered a more nuanced and grounded understanding of TM in general. Findings – Although the results revealed that the concept of TM gained a significant footprint in the studied organisations, the influence of cultural nuances and organisational structural processes restrict the practice of TM, and, indeed, there is a need to have a Chinese characteristic. Research limitations/implications – This research underlies the importance of intensifying critical scrutiny of the relativity of TM, organisational practices and cultural heritage when developing future organisational leaders. Practical implications – The instruments for assessing the phenomena of TM and related concepts encourage legitimacy to extend the limited empirical research with more industries across different geographical regions in China. Originality/value – This paper addresses an under-researched area of world importance, namely, the critical role of TM, which is to optimise these scant resources in the worthy pursuit of economic and political stability in both the domestic and global contexts.